Implementation of a Neuroscience-Based Approach in Environmental Science Learning to Enhance Elementary School Students’ Conceptual Understanding - Rina Purnama Sari; Saiful Bahri; Ida Safitri (CV. Gerasi Insan Nusantara, 2026)
This study aimed to describe the implementation of a neuroscience-based approach in environmental science learning and analyze its contribution to improving the conceptual understanding of fifth-grade elementary school students. The study employed a qualitative descriptive design conducted at SD Negeri 1 Kebun Baru, Langsa City, Aceh Province, during the second semester of the 2025/2026 academic year. The participants consisted of one fifth-grade teacher as the primary informant and 30 fifth-grade students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, document analysis, and a conceptual understanding test. The research instruments included observation sheets, interview guides, documentation checklists, and essay-based conceptual understanding tests. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing, while data credibility was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that the neuroscience-based approach was implemented successfully through five instructional stages: brain engagement, activation of prior knowledge, multisensory learning, collaborative learning, and reflection. The implementation created an active, interactive, and student-centered learning environment that increased students' motivation and engagement. Students demonstrated excellent conceptual understanding, with an average achievement of 89.0%, particularly in explaining concepts, interpreting environmental phenomena, connecting scientific concepts, and applying them to everyday life. Although several challenges were identified, including limited instructional time, learning media preparation, and differences in students' learning abilities, these issues were effectively addressed through flexible classroom management, the use of the school environment as a learning resource, and heterogeneous group learning. Therefore, the neuroscience-based approach represents an effective instructional strategy for enhancing environmental science learning and strengthening elementary school students' conceptual understanding.